Prostacyclin analogues decrease platelet aggregation but have no effect on thrombin generation, fibrin clot structure, and fibrinolysis in pulmonary arterial hypertension: PAPAYA coagulation. (3rd October 2022) - Siniarski, Aleksander; Gąsecka, Aleksandra; Starczyński, Miłosz; Banaszkiewicz, Marta; Darocha, Szymon; Torbicki, Adam; Kurzyna, Marcin; Filipiak, Krzysztof J.; Nessler, Jadwiga; Gajos, Grzegorz
Abstract: Prostacyclin (PGI2 ) analogues (epoprostenol, treprostonil, iloprost) are the cornerstone of pulmonary arterial hypertension (PAH) treatment. PGI2 analogues inhibit platelet reactivity, but their impact on coagulation and fibrinolysis parameters has not been elucidated. We compared platelet reactivity, thrombin generation, clot permeation, and lysis properties in patients with PAH treated with PGI2 analogues (n = 20) and those not receiving PGI2 analogues (n = 20). Platelet reactivity was lower in patients treated with PGI2 analogues, compared to the control group, as evaluated with arachidonic acid (ASPI), adenosine diphosphate (ADP), and thrombin receptor-activating peptide-6 (TRAP) tests ( p = .009, p = .02, p = .007, respectively). In the subgroup analysis, both treprostinil and epoprostenol decreased platelet reactivity to the similar extent. There were no differences regarding thrombin generation, clot permeation, and lysis parameters in patients receiving and not receiving PGI2 analogues ( p ≥ .60 for all). In the subgroup analysis, there were no differences regarding coagulation and fibrinolysis parameters between treprostinil, epoprostenol, and no PGI2 analogues. To conclude, patients with PAH treated with PGI2 analogues have reduced platelet reactivity, but similar clot formation and lysis parameters, compared to patients not receiving PGI2 analogues. Further randomized clinical trials are required to confirm these findings.